Effect of Electroencephalograph Bionic Electrical Stimulation on Brainstem Auditory Evoked Potential and Somatosensory Evoked Potential in Persistent Vegetative State Patients - Yingying NI; Lixia DENG; Liangxiang ZHANG; Congping HUANG; Xiaodi LI; Yunyi LIU; Chengyao QIU; Yigang FENG; Mengliang MA; Chunmei ZHAO; Gang LIU (康复学报)
Objective:To study the effect of electroencephalograph bionic electric stimulating the points of Wangu(GB 12), Tianzhu(BL 10)and Neiguan(PC 6)on the auditory evoked potential(BAEP)and somatosensory evoked potential(SEP)in persistent vegetative state(PVS)patients.Methods:According to random number table method, 60 PVS patients were assigned to electroencephalograph bionic electrical stimulation group(bionic electric group, n=30)and routine treatment group(routine group, n=30). The routine group was given conventional treatment, including basic management, hyperbaric oxygen therapy, stimulating drugs and sensory stimulation, etc.. The bionic electric group received electroencephalograph bionic electrical stimulation therapy on the basis of conventional treatment. The working electrodes were placed on GB 12 and BL 10, and the auxiliary electrodes were placed on PC 6.Each treatment lasted 99 minutes, 30 minutes rest between each treatment.30 days as a therapeutic course. The change of consciousness disturbance was recorded by PVS efficacy assessment scale and the SEP and BAEP were examined by electrical evoked potentiometer on the day before and after the treatment respectively.Results:The total effective rate of the bionic electrical group was 86.67%, which was better than that of normal group(60.00%), and there was significant difference between the two groups(P<0.05). The SEP and BAEP were improved obviously in bionic electrical group, and the efficacy was better than that of routine group(P<0.05).Conclusion:The electroencephalograph bionic electric stimulating GB 12, BL 10 and PC 6 can enhance the effect of promoting revival, and improve the SEP and BAEP in PVS patients to some extent.